If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9q + 7 = 6 + 3(p + -1) Reorder the terms: 7 + 9q = 6 + 3(p + -1) Reorder the terms: 7 + 9q = 6 + 3(-1 + p) 7 + 9q = 6 + (-1 * 3 + p * 3) 7 + 9q = 6 + (-3 + 3p) Combine like terms: 6 + -3 = 3 7 + 9q = 3 + 3p Solving 7 + 9q = 3 + 3p Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9q = 3 + -7 + 3p Combine like terms: 7 + -7 = 0 0 + 9q = 3 + -7 + 3p 9q = 3 + -7 + 3p Combine like terms: 3 + -7 = -4 9q = -4 + 3p Divide each side by '9'. q = -0.4444444444 + 0.3333333333p Simplifying q = -0.4444444444 + 0.3333333333p
| 3x+7=-2x-23 | | Ln(3)+ln(2)=ln(x) | | -7(s+10)+11=-5s-6 | | 6y+10=4+6y+6 | | .55x=2 | | 24-8x=1-11x | | 4-2(3x-5)+x=7(1-3x) | | 1/3h+4=8 | | y=(x-4)/5 | | 3-2(x-1)+4x=5-(2-x) | | -2/3(6x-12y) | | 9(t-9)-11=-6t+10 | | 5w+2=-1+3(w-10) | | X/3-21=14 | | 4-2(3x-5)+x=7-(1-3x) | | X/6-17=14 | | 3x-2(x+4)=2x-3 | | 5x+-5=20 | | 8W+2W-7=23 | | 7+4x-4t=-11 | | 19x-13=25 | | 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) | | 2x+3(1x-10)=45 | | (x^2+1)= | | 2x+3(x-10)=-45 | | y=-0.2*x+520.4 | | 1x-5(x+2)=26 | | 6*6+7= | | 2sen^2x-senx-1=0 |